3D subsurface modelling reveals the shallow geology of Amsterdam. Issue 4 (26th August 2015) - Schokker, J.; Bakker, M.A.J.; Dubelaar, C.W.; Dambrink, R.M.; Harting, R.
Abstract: Amsterdam is situated on the coastal-deltaic plain of the western Netherlands. Its geographical position brought the city prosperity, but also created huge challenges associated with heterogeneous and often adverse ground conditions. This paper explores the geology of Amsterdam to a depth of c. 100 m, based on the output of the 3D geological subsurface models DGM and GeoTOP. The model results are used to create a geological map of the area, to determine the extent and depth of the foundation levels that are in use for buildings in the city centre and to detect the source of filling sand on which part of the more recent expansion of the city was founded. It is shown that subsurface conditions have had a profound effect on both landscape development and historical city growth. Geomodels like DGM and GeoTOP provide an easily accessible way to obtain a better understanding of the shallow subsurface.